Association of the “IUCN vulnerable” spiny rat Clyomys bishopi (Rodentia: Echimyidae) with palm trees and armadillo burrows in southeastern Brazil - Bueno, Adriana A. (2004)
The globally vulnerable Clyomys bishopi, a semi-fossorial and colonial rodent, is apparently limited to cerrado (savannah-like vegetation) physiognomies in São Paulo State, Brazil. The aim of the study was to verify whether the presence of C. bishopi is associated to the occurrence of palm trees (Attalea gearensis, Syagrus loefgrenii) and armadillo burrows. Thirty six quadrats were placed in different physiognomies of cerrado vegetation at Itirapina Ecological Station, southeastern Brazil to survey the number of C. bishopi burrows of individuals of palm trees and burrows of armadillos. There was a strong dependence and association between the number of C. bishopi burrows and all measured variables (Contingency tables and Spearman rank correlations). It is suggested that this rodent can be found in great numbers where palm trees are abundant. The use of armadillo burrows possibly makes the movement of the rodents easier inside their own galleries